THE IMPLEMENTATION OF MARKETING 3.0 TO MSMES IN SURABAYA CITY - Padmalia, Metta; Immanuel, Dewi M. (Jurnal Entrepreneur dan Entrepreneurship, 2018)
The role of Micro, Small and Medium Enterprises (SMEs) is very important as an economic force to countries, especially developing countries like Indonesia. However, the role of the government is still ineffective to support SMEs. As a result, they cannot grow optimally. As one of the economic forces, the role of SMEs is worth considering when ASEAN Economic Community (AEC) begins by the end of 2015. This study aims to investigate how SMEs’ product brands were able to support the economics of the country. Using descriptive qualitative, this study collected the primary data by interviewing five SMEs assisted by Diskoperindag of Surabaya city. This research found that Entrepreneurial Strategy Marketing 3.0 through brand development models 3i (image, identity, integrity) fit the needs of SMEs assisted in Surabaya so that they are able to develop their businesses to face the AEC.